Psychological Impact and their Associated Factors of COVID-19 Pandemic among Nurses of a Metropolitan City of Central Nepal - Lamichhane, Rama Kumari; Dhakal, Bijaya; Thapa, Asha; Sapkota, Kalyan (Journal of College of Medical Sciences-Nepal, 2021)
Introduction: COVID-19 poses a great challenge to the global health system. The nurses worked in COVID ward and fever clinic act as gatekeepers to the health care system in the public health response to COVID-19 epidemic. The consequences of lockdown, quarantine of COVID-19 pandemic has not only caused physical sufferings but also affected the mental health of the nurses around the globe. This study aimed to assess psychological impact and associated factors of COVID 19 pandemic among nurses working in different level of hospital at Bharatpur Municipality Chitwan, Nepal. Methods: A cross-sectional descriptive study was conducted among 150 nurses working in different hospitals of Bharatpur Municipality. Non-probability Purposive Sampling Technique was used and Data was collected via online survey using Google Form questionnaire. COVID-19 peritraumatic distress index (CPDI) questionnaire was used to find out psychological impact. Statistical analysis of data was done using SPSS version 20. Results: Total of 150 nurses were involved in the study where 99.3% were female, 45.3% in the age group of 26-35 years, mean age 27.22±6.612 years, 87.2% bachelor in nursing. Mild to moderate peritraumatic distress was found in 47.33% and 16% of respondents found to have severe distress level. Chi-square test showed that respondents level of knowledge (p=0.003) and presence of chronic disease (p=0.007) was statistically significant with level of distress. Conclusions: Majority of the nurses had some form of psychological distress. Study highlights the need for counseling for distress and mental health during COVID-19 pandemic. A focus on improving mental wellbeing of nurses should be immediately initiated.